First: eliminate the parenthesis > use the distribution metho by multiplying the outer term with the inner terms...
3(x) + 3(-4) > 7x - 9
3x - 12 > 7x - 9
*Combine "like" terms by...
Sec: adding "12" to both sides...
3x - 12 + 12 > 7x - 9 + 12
3x > 7x + 3
*Subtract "7x" from both sides...
3x - 7x > 7x - 7x + 3
- 4x > 3
Third: isolate "x" on one side > divide both terms by "-4"...
- 4x/-4 > 3/-4
*When you have an inequality & your dividing by a negative number, always change the inequality sign...
x < - 3/4
2007-01-29 11:44:46
·
answer #1
·
answered by ♪♥Annie♥♪ 6
·
1⤊
0⤋
7x - 7 = 3x + 20 4x = 27 x= 27 / 4 x - 9 = 6x + 7 -5x = sixteen x = -sixteen / 5 10x - 2/5 = 3 10x = 15/5 + 2/5 10x = 17/5 x = 17 / 50 3 (x - 5) = x - 20 3x - 15 = x - 20 2x = -5 x = -5/2 4 (x + 6) = 23 4x + 24 = 23 4x = -a million x = -a million / 4 2 (x - 3) + x = 9 2x - 6 + x = 9 3x = 15 x = 5
2016-10-16 06:52:04
·
answer #2
·
answered by machey 4
·
0⤊
0⤋
3(x-4)>7x-9
Treat this like an equation
First simplify
3x-12>7x-9
get like terms on same sides
-3>4x
divide by 4
x < -3/4
2007-01-29 11:35:57
·
answer #3
·
answered by ignoramus 7
·
1⤊
0⤋
3(x-4)>7x-9
you multiply anything that touches the parntheies
3x-12>7x-9
-3x -3x
__ __
x 4x
-12>4x-9
+9 +9
-3 0
-3>4x
then divide four x into 4 and -3
2007-01-29 11:45:03
·
answer #4
·
answered by Ian W 2
·
0⤊
0⤋
x<-3/4
2007-01-29 11:41:13
·
answer #5
·
answered by ema 3
·
0⤊
0⤋
3x-7x>12-9 or -4x>3 or x>-3/4
2007-01-29 11:37:04
·
answer #6
·
answered by 1ofSelby's 6
·
0⤊
0⤋
3(x-4) > 7x - 9
Distribute the 3
3x - 12 > 7x - 9
Add 12 to each side
3x > 7x + 3
Subtract 7x from each side
-4x > 3
Divide both sides by -4 (remember to flip the inequality sign)
x < -3/4
2007-01-29 11:34:07
·
answer #7
·
answered by MsMath 7
·
1⤊
1⤋
3(x-4)>7x-9
3x-12 > 7x-9
-3 > 4x
4x < -3
x < -3/4
2007-01-29 11:33:26
·
answer #8
·
answered by Bill F 6
·
1⤊
0⤋
3(x-4)>7x-9
3x-12>7x-9
3x>7x+3
-4x>3 (remember when you divide or multiply by a negative, you have to switch the greater than/less than sign)
x<-3/4
2007-01-29 11:36:11
·
answer #9
·
answered by Mr. Irrelevant 3
·
0⤊
0⤋
3(x-4) [is greater than] 7x-9
= (3x-12) > (7x-9)
-3x -3x
=(-12) > (4x-9)
-9 -9
=(-21) > (4x)
____ _____
4 4
therefore -5.25 = x
so your question now becomes
-21 > -21
and as u can see there equal.
2007-01-29 11:57:49
·
answer #10
·
answered by Kieren S 1
·
0⤊
0⤋